Quelques aspects sémantico-syntaxiques des ‘verbes en gl-’ de l’anglais ayant trait à la notion de ‘lumière’ et / ou de ‘vision’ - Dennis Philps (Anglophonia)
In this paper, I look at certain semantico-syntactic aspects of the heuristically established subset of English ’gl-verbs’ related to ’light’ and/or ’vision’ (glance, glare, glimpse, glow, etc.), namely transitivity, agency, telicity, causativity, invariance, and participant roles. On the basis of this study, I claim that a cognitive process involving the conceptual projection of eye-related capacities and properties onto intra-somatic and extra-somatic target domains perceived as homologous results in the transcoding of these capacities and properties into specific grammatical relations.